2007
DOI: 10.1039/b711978j
|View full text |Cite
|
Sign up to set email alerts
|

Entangled palladium nanoparticles in resin plugs

Abstract: Palladium nanoparticles were entrapped within resin plugs and used in a range of ligand-free cross-coupling reactions; the convenient modular format of the resin plug enhanced resin handling and allowed the catalysts to be easily recovered and multiply reused.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 21 publications
(5 reference statements)
1
26
0
Order By: Relevance
“…The shell can be composed of different materials, among them the native iron oxide is attractive and intensively studied for its almost unavoidable formation and good performance to control the oxidation of iron core [12 15]. The aggregation of ZVINs, mainly derived from the behavior to decrease their surface free energy can be, to a great extent, inhibited by dispersing them with organic or inorganic protective reagents such as polymers [16], surfactants [17], dendrimers [18], resins [19], aluminas [20], active carbons [21], zeolites [22], and clay minerals [23]. Compared with other protective reagents, inorganic chemically inert clay minerals are more cost-effective and environment-friendly, and they are also commonly used as supports for nanoparticles.…”
mentioning
confidence: 99%
“…The shell can be composed of different materials, among them the native iron oxide is attractive and intensively studied for its almost unavoidable formation and good performance to control the oxidation of iron core [12 15]. The aggregation of ZVINs, mainly derived from the behavior to decrease their surface free energy can be, to a great extent, inhibited by dispersing them with organic or inorganic protective reagents such as polymers [16], surfactants [17], dendrimers [18], resins [19], aluminas [20], active carbons [21], zeolites [22], and clay minerals [23]. Compared with other protective reagents, inorganic chemically inert clay minerals are more cost-effective and environment-friendly, and they are also commonly used as supports for nanoparticles.…”
mentioning
confidence: 99%
“…The cross-linked captured palladium resin (XL-QPPd) was readily prepared via a 3-step procedure [25, 26]. This was based on physical entrapment by the polymers and also on electronic interactions between the electrons of the aryl rings of polystyrene-based polymers and vacant orbitals onto the catalysts, resulting in stronger connections between the components [27, 28].…”
Section: Resultsmentioning
confidence: 99%
“…PdNPs have been entangled in resin plugs following a procedure consisting of loading an aminomethylated styrene resin with Pd(II) acetate, reduction to Pd(0) with hydrazine and cross-linking and entanglement by reaction of the amino groups with succinyl chloride. 71 The resulting plugs were used as supported catalysts (9.8 mol% Pd) in several palladium-catalyzed C C bond-forming reactions such as the Sonogashira coupling of aryl iodides and phenylacetylene in the presence of potassium carbonate in DMF as solvents at 80 ‱ C. Recycling experiments showed that yields remained unaltered after four runs, and leaching determinations after using this catalyst in a Heck reaction in DMF at 115 ‱ C showed 0.37 ppm of Pd(0) content in the solution at the fifth run.…”
Section: Formula 23mentioning
confidence: 99%